Phosphine ligand and base-free, Pd-catalyzed oxidative cross-coupling reaction of arylboronic acids with arylmercuric acetates - Emmanuvel, Lourdusamy; Sudalai, Arumugam (Arkivoc, 2007)
Arylmercuric acetates have been found to undergo Suzuki type cross coupling reactions with arylboronic acids catalyzed by palladium salts in non-polar solvents under ambient conditions to give biaryl derivatives in high yields. The reaction is mild and does not require any organic or inorganic base nor a phosphine ligand.
Keywords: Arylboronic acid; arylmercuric acetate; palladium salts; Suzuki coupling